Information-Based Instruments for Improved Urban Management - Deichmann, Uwe; Lall, Somik V.; Suri, Ajay; Rajoria, Pragya (World Bank, Washington, DC, 2014)
The task of urban managers is to ensure the provision of basic urban services, such as water, waste removal, security, transport, and an environment conducive to economic activity, while maintaining fiscal sustainability of city operations. City managers in developing countries face increasing pressure in achieving these goals because of rapid urbanization, the larger responsibilities following decentralization, and the economic challenges of globalization. Based on experience in Bangalore, India, the authors argue that effective, forward-looking urban management requires a much better information infrastructure than is currently available in most cities.